Integrated closure planning and closure criteria: the road to success … criteria - Erasmus, J.; Coetzer, N. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Mine closure planning and execution should be from ‘cradle to cradle’, where all mine-planning processes are integrated with closure. The integrated closure planning system (ICPS), developed in 2014 at Anglo American (AA) mining operations, aimed to provide a consistent approach over projects life cycles for the reporting and management of longterm closure liabilities. ICPS aided in achieving the goal of ensuring that a positive and sustainable legacy is left for host communities after operations have closed. The AA Mine Closure Toolbox (MCT) was developed in 2007 with an updated version released in 2013 (version 2). A further updated version integrating the ICPS and International Council for Mining and Metals (International Council for Mining and Metals [ICMM]) best practice principles was released in 2019 known as MCT Version 3. These documents together with International Finance Corporation standards form the current industry best practice (IBP) for integrated mine closure planning and emphasises the importance of a multidisciplinary approach and continuous refinement of both rehabilitation and closure criteria, and success criteria. Ultimately, implementing the closure criteria, dictates the closure liabilities and financial provisions necessary to successfully rehabilitate mining operations, as per various African case studies. This paper will focus on the road to success by developing closure criteria using a risk-based approach and refined through benchmarking, closure risk assessments, closure gap analyses and closure criteria effectiveness reviews. This will aid the reduction of potential residual risks to acceptable levels and achieving the defined success criteria. Success criteria must complement and fully align with the closure vision, objectives and closure criteria. In countries lacking mine closure jurisdiction and relevant legal frameworks, IBP for mine closure should be implemented. South African legislation and regulations for mine closure can be seen as world-leading which directly assists integrated closure planning, ensuring the closure criteria would fulfil the defined success criteria and lead to successful rehabilitation and facilitate final site relinquishment.